The Use Of Modern Technologies In The Exchange Of Time And Cost To Complete Projects In A Foggy Environment - Abud Almunaam Kidam Hemidi; BASHER FAESIL Mohammed; Ali Hussen Abd Ali (Journal of Madenat Alelem University College, 2018)
The problem of blurry in the completion of projects, especially building projects of the important problems that should be appropriate solutions to them in order to obtain an integrated and successful project and within the standards required by committing to the time of completion and investment resources available to the implementing agency of the best investment, the problem is the result of information or data It is necessary to find a realistic and practical way to address this problem through the application of the concept of fog theory developed by the world (Zadeh. L. A.) and Working with the logic tools in the MATLAB program and employing the modern Time-Cost Trade-Off technology to determine the optimum time for project completion and the lowest possible cost increase using project management software including MS Project .